2014
DOI: 10.1111/cei.12346
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D binding protein and vitamin D in human allergen-induced endobronchial inflammation

Abstract: SummaryAllergic asthma is a chronic disease of the airways associated with airway hyperresponsiveness, a variable degree of airflow obstruction, airway remodelling and a characteristic airway inflammation. commercial laboratory using the liquid chromatography-mass spectrometry (LC/MS) technique. VDBP (median 2·3, range 0·2-7·1 μg/ml), 25(OH)D3 (median 0·060, range < 0·002-3·210 ng/ml) and 1,25(OH)2D3(median < 0·1, range < 0·1-2·8 pg/ml) were significantly elevated in BALF 24 h but not 10 min after allergen ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 29 publications
1
16
0
2
Order By: Relevance
“…These findings suggest that these factors may play a role in the late-phase response in asthma. 55 In a Korean study, it was found that low serum 25(OH)D levels were positively associated with total IgE levels which varied based on gender and sensitization to Dermatophagoides farina . Overall, patients with a history of asthma or atopic dermatitis had significantly lower serum 25(OH)D levels than patients who did not suffer from these conditions.…”
Section: Adultsmentioning
confidence: 99%
“…These findings suggest that these factors may play a role in the late-phase response in asthma. 55 In a Korean study, it was found that low serum 25(OH)D levels were positively associated with total IgE levels which varied based on gender and sensitization to Dermatophagoides farina . Overall, patients with a history of asthma or atopic dermatitis had significantly lower serum 25(OH)D levels than patients who did not suffer from these conditions.…”
Section: Adultsmentioning
confidence: 99%
“…[24][25][26][27][28][29][30] The iCOGs array directly genotyped rs12794714 and rs2282679; rs7944926 was the best imputed DHCR7 SNPs (imputation quality score of 0.92) described by previous study. 31 We were unable to include rs6013897 in …”
Section: Snp Selection Criteriamentioning
confidence: 99%
“…18 A recent study showed increased levels of vitamin D-binding protein and 25-hydroxyvitamin D in bronchoalveolar lavage fluid after allergen challenge, suggesting a role for these factors in allergic late-phase reactions. 19 A low serum vitamin D level may represent a marker of Western life style. Modern life is associated with less time spent outdoors; altered nutrition; increased obesity; exposure to cigarette smoking, ultrafine particles, and ozone; and inadequate physical activity.…”
Section: Introductionmentioning
confidence: 99%